Papers of Sir Anthony Musgrave (as filmed by the AJCP) [M412] - Musgrave, Anthony, Sir, 1828-1888.; Griffith, Samuel, Sir, 1845-1920.; Musgrave, Jeannie Lucinda, Lady.; National Library of Australia; Australian Joint Copying Project; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
1) Letters of commission and associated instructions 1862-83, appointing Musgrave to his various official positions. 2) Memorial 1883, signed by J.I. Wigham and all the "principal ladies" of Portland, Jamaica. 3) Correspondence, including letters from Sir Alfred Stephen to Dudley Field; 15 letters 1890-1901 from Sir Samuel Griffith to Lady Musgrave, with references to Federation and Australian political and public figures; correspondence 1888 between Colonel G.A. French and W.A. B. Musgrave, re a Captain Draper; correspondence 1870-1916 re journal articles on economic topics by Sir Anthony Musgrave. 4) Schedule of petitions, telegrams and letter, 1884, re Bernard Williams and Neil McNeil, (found guilty in Nov. 1884 of the shooting of a native of the Solomon Islands). 5) Diary 1888, kept by Lady Musgrave; book containing items related to the death of her husband in 1888. 6) Correspondence 1910-12 concerning memorials to Musgrave with photographs of the memorials.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M412.
Also available online
Microfilm copy of originals held by Duke University, Durham, North Carolina, 27706, U.S.A.
Keywords: Musgrave, Anthony, -- Sir, -- 1828-1888 -- Archives; Musgrave, Jeannie Lucinda, -- Lady, -- Archives; Griffith, Samuel, -- Sir, -- 1845-1920 -- Correspondence; Governors -- Archives; Governors' spouses -- Archives; Australia -- Politics and government -- 1891-1901.